Zapisz podane wyrażenia w najprotszej postaci i oblicz wartość podanych wyrażeń a)4(2x-4y) + 3(x+y). dla x= 1 , y=2 b)3(a-2b)(a+2b) - 2(a+2b)^2 + 8ab. dla a= -2, b=0,5 c)4a(5a-2)-(2a^2 -1+3a). dla a=3
^2 to do potęgi 2
mangosia1a)4(2x-4y) + 3(x+y). dla x= 1 , y=2 8x-16y+3x+3y=11x-13y=11*1-13*2=11-26=-15 b)3(a-2b)(a+2b) - 2(a+2b)^2 + 8ab. dla a= -2, b=0,5 3a^2-12b^2-2a^2-8ab-8b^2+8ab=a^2-20b^2=-2^2-20*0,5^2=4-20*0,25=4-5=-1
c)4a(5a-2)-(2a^2 -1+3a). dla a=3 20a^2-8a-2a^2+1-3a=18a^2-11a+1=18*9-33+1=162-33+1=130
8x-16y+3x+3y=11x-13y=11*1-13*2=11-26=-15
b)3(a-2b)(a+2b) - 2(a+2b)^2 + 8ab. dla a= -2, b=0,5
3a^2-12b^2-2a^2-8ab-8b^2+8ab=a^2-20b^2=-2^2-20*0,5^2=4-20*0,25=4-5=-1
c)4a(5a-2)-(2a^2 -1+3a). dla a=3
20a^2-8a-2a^2+1-3a=18a^2-11a+1=18*9-33+1=162-33+1=130